Ubicamos lugares de nuestro entorno y describimos los desplazamientos que usamos para movilizarnos - Cornejo Rodríguez, Yvon Yngrid (2020)
This Professional Proficiency work was developed for children in the fourth grade of primary education in the 81017 Santa Edelmira educational institution of Trujillo city in 2019, with the topic entitled, We locate places around us and describe the displacements used to mobilize, in which the competition is going to develop. solving problems of form, movement and location In the development of the session. It was done taking into account the didactic processes in the area of mathematics, such as: familiarization with the problem, search and execution of strategies, socialization of representations, reflection and formalization, and the approach of other problems, as well as the capabilities: Model objects with geometric shapes and their transformations, communicate their understanding of geometric shapes and relationships, They use strategies and procedures to orient themselves in space and argue statements about geometric relationships, using everyday language and concrete representations and drawings. The strategies used were designed to promove the active and meaningful participation of all students, as well as rescue the use of new learning in their daily lives It is intended at all times to maintain the interest and motivation of the student for the topic to be developed since it is a very important area that which seeks for students to develop life skills.